Collaborating Against Child Abuse 2017
DOI: 10.1007/978-3-319-58388-4_7
|View full text |Cite
|
Sign up to set email alerts
|

Child Forensic Interviewing in Finland: Investigating Suspected Child Abuse at the Forensic Psychology Unit for Children and Adolescents

Abstract: PreambleIn Finland, specialised university hospital units have taken on much of the role of the Barnahus in other Nordic countries, ensuring a childfriendly and expert environment for child interviews in cases of suspected crimes against children. The personnel consist of multi-professional teams including expertise in forensic psychology, paediatrics, child psychiatry and social work. There are units in the country's five university hospitals, thus covering the whole country. The units provide expert assistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 22 publications
0
24
0
3
Order By: Relevance
“…Training investigative interviewers to successfully implement guidelines for investigative interviewing requires extensive training, continuous feedback, and follow‐up sessions (Powell, 2018). In Finland, police officers who interview children suspected of being victims of sexual or physical violence are required to complete a year‐long training period (Korkman, Pakkanen, & Laajasalo, 2017). The training period for Finnish asylum officials is, by contrast, only 4 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Training investigative interviewers to successfully implement guidelines for investigative interviewing requires extensive training, continuous feedback, and follow‐up sessions (Powell, 2018). In Finland, police officers who interview children suspected of being victims of sexual or physical violence are required to complete a year‐long training period (Korkman, Pakkanen, & Laajasalo, 2017). The training period for Finnish asylum officials is, by contrast, only 4 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…This training may be especially important not only given the central role of prosecutors in investigations involving children but also since psychological expertise is not regularly used during CSA investigations or court proceedings in Sweden. In contrast to for example Finland (see Korkman, Pakkanen, & Laajasalo, 2017), there is no system in place for involving psychologists specialized in child interviewing or children's testimony during the investigative stage, even if clinical psychologists may be available at the Barnahus. As opposed to many other Western countries, psychological expertise is not frequently used in court either, and a recent study revealed that expert witnesses from the field of psychology only testified in 5% Swedish court cases concerning alleged CSA of a child below the age of 7 (Ernberg, Magnusson, Landström, & Tidefors, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…S. Johansson and K. Stefansen model since 2014, although it implemented a similar model in forensic-psychology units at larger hospitals as early as 2008 (see Korkman, Pakkanen, and Laajasalo 2017). Even though the time of establishment and numbers of national Barnahus differ across the Nordic countries, the diffusion of the Barnahus model has been rapid and extensive within the Nordic region (Johansson et al 2017b).…”
Section: The Nordic Phase: Successive Policy Development and A Favourmentioning
confidence: 99%